Leukocyte telomere length is inversely associated with post-load but not with fasting plasma glucose levels. Issue 7 (April 2017) - Khalangot, Mykola; Krasnienkov, Dmytro; Vaiserman, Alexander; Avilov, Ivan; Kovtun, Volodymir; Okhrimenko, Nadia; Koliada, Alexander; Kravchenko, Victor
Type 2 diabetes mellitus is characterized by shorter leukocyte telomere length, but the relationship between leukocyte telomere length and type 2 diabetes mellitus development is rather questioned. Fasting and post-load glycaemia associated with different types of insulin resistance and their relation with leukocyte telomere length remains unknown. We compared leukocyte telomere length and fasting or post-load glucose levels in persons who do not receive glucose lowering treatment. For 82 randomly selected rural residents of Ukraine, aged 45+, not previously diagnosed with type 2 diabetes mellitus, the WHO oral glucose tolerance test and anthropometric measurements were performed. Leukocyte telomere length was measured by standardized method of quantitative monochrome multiplex polymerase chain reaction in real time. Spearman's or Pearson's rank correlation was used for correlation analysis between fasting plasma glucose or 2-h post-load plasma glucose levels and leukocyte telomere length. Logistical regression models were used to evaluate risks of finding short or long telomeres associated with fasting plasma glucose or 2-h post-load plasma glucose levels. No association of fasting plasma glucose and leukocyte telomere length was revealed, whereas 2-h post-load plasma glucose levels demonstrated a negative correlation ( P < 0.01) with leukocyte telomere length. Waist circumference and systolic blood pressure were negatively related ( P = 0.03) with leukocyte telomere length in men. Oral glucose tolerance test result-based glycemic categories did not show differences between mean leukocyte telomere length in categories of normal fasting plasma glucose and 2-h post-load plasma glucose (NGT, n = 33); diabetes mellitus (DM), n = 18 and impaired fasting glucose/tolerance (IFG/IGT, n = 31) levels. A correlation relationship between leukocyte telomere length and 2-h post-load plasma glucose level in NGT; IFG/IGT and DM groups ( P = 0.027; 0.029 and 0.049, respectively) was revealed; the association between leukocyte telomere length and fasting plasma glucose was confirmed in DM group only ( P = 0.009). Increase of 2-h post-load plasma glucose (but not fasting plasma glucose) level improves the chances of revealing short telomeres: OR 1.52 (95% CI 1.04–2.22), P = 0.03. After the adjustment for age, gender, waist circumference, systolic blood pressure, and fasting plasma glucose, these phenomena remain significant. We conclude that 2-h post-load plasma glucose but not fasting plasma glucose is inversely associated with leukocyte telomere length. Impact statement: Contradictory epidemiologic data have been obtained about the link between the leucocyte telomere length (LTL) and diabetes. Type 2 diabetes (T2D) is likely to be pathophysiologically heterogeneous, but comparison of the association of LTL separately with fasting plasma glucose (FPG) and 2-h post-load plasma glucose (2hPG) levels has not been done before. Thus, the study of LTL changes associated with different types of hyperglycaemia, that largely determine the heterogenity of T2D is important. In a population-based study of rural Ukrainians, we were the first to demonstrate that the increase of 2hPG (but not FPG) level increases the chances of revealing short telomeres. The obtained data can help to clarify the relationship between the LTL shortening and different conditions of the insulin resistance (mainly liver resistance in high FPG and mostly muscle and adipose tissue resistance in high 2hPG).